ANALYSIS OF SERVICE QUALITY AND HOSPITAL IMAGE ON OUTPATIENT SATISFACTION AT BHAYANGKARA TK II SARTIKA ASIH HOSPITAL BANDUNG CITY - santo hegiarto, aldy; Suhanda, Suhanda (Universitas Islam Lamongan, 2024)
Competition in the healthcare industry is currently very tight. This is due to the increasing number of clinics and hospitals that are established, as well as the increasing number of people who use hospitals to get health services. This is proportional to the increasing public awareness of health services. In addition, the presence of private and government-owned hospitals, doctors' practices and midwives in every area where people live, will add to the high level of competition in this industry. A pre-survey was conducted to determine the level of satisfaction of outpatients. The problem is service quality and hospital image on outpatient patient satisfaction at Bhayangkara Sartika Asih Hospital, Bandung City. This study aims to analyze using the Qualitative Descriptive method. By conducting direct interviews at the research location, namely Bhayangkara Hospital TK II Sartika Asih Bandung City, the results of in-depth interviews with all informants show that the hospital service system needs improvement, especially by adding Human Resources for services in the outpatient room, in order to support the quality of quality service. overall. Overall.